Smart mobile apps for supporting product design and decision-making in the era of mass customisation. Issue 7 (3rd July 2017) - Mourtzis, D.; Doukas, M.; Vandera, C.
Abstract : Nowadays, manufacturing industries face the need to rapidly and effectively adapt to the fast changing market demands that are affected by globalisation, economic instability and customer needs towards higher product variety. Rigid centralised decision-making and IT infrastructures are no longer a viable solution for a company to withstand the globalised market pressure. Information on core activities of a company, such as the manufacturing network design, needs to be constantly available to managers and planners to increase awareness and supervision efficiency. Mobility and remote decision-making is steadily gaining ground as the standard practice in the inter-connected business world. Moreover, the personalisation of products tailored to the individual needs and preferences of the customers can now be achieved through mobile applications, namely apps. Yet, the establishment of mobile apps in the manufacturing domain is still premature. The work proposed in this article presents a set of mobile apps developed to support the customer integration in the product design phase and subsequently the design of the manufacturing network. The applicability of the developed mobile apps is demonstrated through a pilot case from the automotive sector, and specifically, from the customisation of accessories and car aesthetics.